In tennis, do smashes win matches? - Budrus, S.; Vander Plas, S.; Cook, D. (Significance, 2013)
It is summer, and Wimbledon and the French and US Opens are with us. In tennis, does the man with the fastest serve win? And can you make too few unforced errors for success?